Sobereign Writing - Rocha, Delmiro (Escritura e Imagen, 2012)
We approach the deconstruction of sovereignty from the slant point of view of the sovereign madman. We base this approach on the reading of King Lear by Shakespeare, a tragedy in which sovereignty is divided twice, at the beginning and the end of the play, and which opens the possibility of a contemporary reading of it around two fundamental axes: madness and death. Two sovereign madnesses and three sovereign deaths.